Planktonic foraminifera in the seafloor of Wulan Estuary of Demak, Central of Java, Indonesia. Issue 1 (November 2021) - Hartati, R; Zainuri, M; Endrawati, H; Widianingsih, W; Manuhuwa, B A; Pribadi, R
Abstract: Planktonic foraminifera are marine heterotrophic protists that surround their unicellular body with elaborate calcite shells. They exhibit a range of trophic behaviors from indiscriminate omnivory to selective carnivory. The species inhabit the photic zone with various density. The present work was aimed to identify and determine the density of planktonic foraminifera in the seafloor of Wulan Estuary of Demak regency, Central of Java, Indonesia. The sediment in the seafloor was taken using van veen grab sampler from 5 stations based on their position in the estuary. Upon arriving in the laboratory, the samples was washed and sun-dried. The dry sediment samples then were ground and sieved with following mesh sizes, i.e. 0.063, 0.125, and 0.250 mm and put in the plastics sample. The samples of foraminiferan then were hand picking in the picking tray. Classification of planktonic foraminifera is based entirely on the properties of their shells, i.e. wall composition and structure, chamber shape and arrangement, the shape and position of any apertures, surface ornamentation, and other morphologic features of the shell. The present work found 7 genera of planktonic foraminifera from the seafloor of Wulan estuary, i.e. Candeina, Globigerina, Globigerinoides, Globorotalia. Neogloboquadrina, Orbulina, and Pulleniatina. The lowest density was found in the Station 1 ( 7429 indv.m −2 ) which was the furthest station from estuary, and the highest density was 7886 indv.m −2 present in Station 3 which was the closest to estuary. Since all seafloor were consisted of silt sediment, these density differences were more influenced by salinity of the water.